2021
DOI: 10.1021/acsaem.1c01941
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size and Particle-Size Distribution Effects on Li+ Extraction/Insertion Kinetics for Li-Rich Mn-Based Oxides

Abstract: A series of Li-rich Mn-based layered material Li1.2Ni0.13Co0.13Mn0.54O2 (LMR) with different particle sizes and particle-size distributions (PSDs) have been successfully synthesized via a combustion method using different manganese sources. The particle size of the N-LMR material prepared using Mn­(NO3)2·4H2O as the manganese source is the smallest, and its PSD range is the narrowest among all of the samples. The unique particle size and PSD have a great influence on the electrochemical kinetics of Li-ion extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For the sample LMR, all of the dominant diffraction peaks and apparent splitting peaks of 006/102 and 018/110 of both materials can be indexed to the R-3m space group of the hexagonal α-NaFeO 2 -type layered structure, without an obvious impurity phase [ 35 , 36 ]. The weak superstructure reflections of both materials between 20° and 25° indicate the existence of the Li 2 MnO 3 phase, which is the typical feature of lithium-rich cathode materials, arising from the superlattice ordering of Li and Mn in the transition metal layers of the Li 2 MnO 3 phase [ 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the sample LMR, all of the dominant diffraction peaks and apparent splitting peaks of 006/102 and 018/110 of both materials can be indexed to the R-3m space group of the hexagonal α-NaFeO 2 -type layered structure, without an obvious impurity phase [ 35 , 36 ]. The weak superstructure reflections of both materials between 20° and 25° indicate the existence of the Li 2 MnO 3 phase, which is the typical feature of lithium-rich cathode materials, arising from the superlattice ordering of Li and Mn in the transition metal layers of the Li 2 MnO 3 phase [ 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Fang et al. synthesized a series of Li‐rich Mn‐based layered materials (Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 ) with different particle sizes and size distributions and demonstrated that the Li‐ion extraction/insertion kinetics were faster for smaller particles [8a] . Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Lithium‐ion batteries (LiBs) were the first commercialized battery in 1991. Undeniably, LiBs have the lowest redox potential (−3.04 V vs the standard hydrogen electrode) and a splendid theoretical capacity (3860 mAh g −1 ), [ 5 ] which have a rapid development and various cathodes, such as Li‐rich cathode material, [ 6 ] LiCoO 2 , [ 7 ] LiFePO 4 , [ 8 ] and LiMn 2 O 4 . [ 9 ] Nevertheless, some issues have occurred in commercialized LiBs because of organic electrolytes.…”
Section: Introductionmentioning
confidence: 99%